In vitro ruminal fermentation characteristics of gum arabic under concentrate and forage substrate conditions. (27th October 2021) - Han, Hongyan; Yamanaka, Sayaka; Tsukahara, Takamitsu; Hotta, Yoshio; Takagi, Tokuji; Kumagai, Hajime
Abstract: Gum arabic (GA) has potential rumen modifier functions. This is the first study to investigate the in vitro ruminal fermentation characteristics of GA. Rumen fluid was collected from ruminal fistulated wethers; rolled barley and ryegrass straw were used as substrates for concentrate and forage conditions, respectively. Besides incubating with the substrates alone (control), GA or potato starch (PS) was added at 0.2%, 1.0%, and 2.0% along with substrates. Under the concentrate substrate condition, GA treatments showed higher total gas production in 24‐h incubation, but lower methane production in 24‐ and 48‐h incubation compared with PS treatments ( p  < 0.05). The 1.0% and 2.0% GA and 0.2% and 1.0% PS treatments showed higher dry matter and neutral detergent fiber digestibility and lower NH3 ‐N, and higher short chain fatty acid concentrations compared with the control at 24‐h incubation ( p  < 0.05). The GA treatments also showed a lower acetate/propionate ratio than PS treatments at 48‐h incubation ( p  < 0.01). Under the forage substrate condition, the treatment effects were not significant, except for a higher proportion of propionate with GA than with PS at 24 and 48 h of incubations. We thus concluded that GA supplement may exert potential rumen modifier effects particularly under concentrate feeding condition.